(untitled) (INCH : Journal of Infant and Child Healthcare, 2022)
The maternal mortality rate in Indonesia reaches 305 out of 100,000 live births. One of the indirect causes is anemia caused by the non-compliance of pregnant women in consuming Fe tablets. One of the factors that increase the compliance of pregnant women is husband’s support. This study aims to determine the relationship of husband’s support to pregnant women’s compliance in consuming iron tablets (fe). The method used in this study was an analytical method with accidental sampling. This research was obtained in the Work Area of ​​the Kilan Health Center in 2022, amounting to 83 respondents by distributing questionnaires. The results of the study the majority of husbands supported the number of 77 people (92.8%). Meanwhile, the majority of pregnant women complied with the number of 75 people (90.4%). The results of statistical analysis showed p value 0.00 ≤ 0.05. The conclusion of this study is that there is a relationship between husband’s support and adherence to pregnant women in consuming iron (Fe) tablets in the Kilan Health Center Work Area in 2022